Cultural Adaptation of a Neurobiologically Informed Intervention in Local and International Contexts. Issue 158 (15th December 2017) - Pakulak, Eric; Hampton Wray, Amanda; Longoria, Zayra; Garcia Isaza, Alejandra; Stevens, Courtney; Bell, Theodore; Burlingame, Sarah; Klein, Scott; Berlinski, Samuel; Attanasio, Orazio; Neville, Helen
Abstract: The relationship between early adversity and numerous negative outcomes across the lifespan is evident in a wide range of societies and cultures (e.g., Pakulak, Stevens, & Neville, 2018). Among the most affected neural systems are those supporting attention, self‐regulation, and stress regulation. As such, these systems represent targets for neurobiologically informed interventions addressing early adversity. In prior work with monolingual native English‐speaking families, we showed that a two‐generation intervention targeting these systems in families improves outcomes across multiple domains including child brain function for selective attention (for detail, see Neville et al., 2013). Here, we discuss the translation and cultural adaptation (CA) of this intervention in local and international contexts, which required systematic consideration of cultural differences that could affect program acceptability. First, we conducted a translation and CA of our program to serve Latino families in the United States using the Cultural Adaptation Process (CAP), a model that works closely with stakeholders in a systematic, iterative process. Second, to implement the adapted program in Medellín, Colombia, we conducted a subsequent adaptation for Colombian culture using the same CAP. Our experience underscores the importance of consideration of cultural differences and a systematic approach to adaptation before assessing the efficacy of neurobiologically informed interventions in different cultural contexts.